'Do UC the melanoma?' Recognising the importance of different lesions displaying unevenness or having a history of change for early melanoma detection. (19th February 2014) - Yagerman, Sarah E; Chen, Lucy; Jaimes, Natalia; Dusza, Stephen W; Halpern, Allan C; Marghoob, Ashfaq
Abstract Background/Objectives Many melanomas are of a diameter smaller than 6 mm and may lack classical asymmetry, border irregularity and colour variegation (ABCD). The objectives of this article are to characterise the fidelity of melanomas diagnosed in a high‐risk clinic to the ABCD and to review potential methods for early clinical detection of melanoma. Methods All cases of primary melanoma diagnosed by one clinician at the Memorial Sloan–Kettering Cancer Center over the past 11 years were evaluated for the presence of the ABCD. The melanomas were analysed for asymmetry of contour, unevenness in distribution of colours and textures, border irregularity, number of colours present and diameter. Results In all, 236 melanomas were analysed. Of these, asymmetry of contour was present in 65% and 94% demonstrated unevenness in the distribution of colours and textures. The borders were regular in 12% of the melanomas and colour variegation was present in 63%. In total, 28% of the lesions were small, with a diameter less than 6 mm. This study was limited by the subjectivity of clinical lesion analysis. Conclusion We put forward for your consideration a new mnemonic: 'Do UC (different, uneven, changing) the melanoma?' This mnemonic encompasses differential, analytical and comparative cognition strategies for an enhanced early detection of melanoma.